Chemical dechlorination of hexachlorobenzene with polyethylene glycol and hydroxide: Dominant effect of temperature and ionic potential - Xiao, Ye (Nature Publishing Group, 2014)
Persistent organic pollutants (POPs) originating from POP waste are playing an increasingly important role in the elevation of regional POP levels. In this study we realized the complete dechlorination of high concentration hexachlorobenzene (HCB) waste in the presence of polyethylene glycol and hydroxide, rather than using conventional high temperature incineration. Here, we demonstrate the dominant effect of temperature and hydroxide on HCB dechlorination in this process. Complete dechlorination of HCB was only observed at temperature about 200°C or above within 4 h reaction, and the apparent activation energy of this process was 43.1 kJ/mol. The alkalinity of hydroxides had notable effects on HCB dechlorination, and there was a considerable linear relationship between the natural logarithm of the HCB dechlorination rate constant and square root of the ionic potential of metal cation (R(2) = 0.9997, p = 0.0081, n = 3). This study highlights a promising technology to realize complete dechlorination of POP waste, especially at high concentrations, in the presence of PEG in conjunction with hydroxide.